PoreDesigner for tuning solute selectivity in a robust and highly permeable outer membrane pore - Ratul Chowdhury; Tingwei Ren; Manish Shankla; Karl Decker; Matthew Grisewood; Jeevan Prabhakar; Carol Baker; John H. Golbeck; Aleksei Aksimentiev; Manish Kumar; Costas D. Maranas (Nature Communications, 2018)
Monodisperse angstrom-sized membrane proteins, found in biological membranes, are difficult to implement in synthetic industrial membranes. Here authors present a pore design procedure, to redesign the robust beta-barrel Outer Membrane Protein F (OmpF) with specific solute selectivity.